The rural delivery system and the various entities involved in rural development - Hooja, Rakesh (2010)
Brining government closer to the rural people improves the match between diverse local preferences and public services. In a country of India's size and diversity, rural development is humongous and highly complex endeavour. Rural development has of course to be planned and pursued within national development model subsuming the interdependent and interactive growth of both rural and urban areas. There is a need for comprehensive planning for rural development which postulates to involve itself not only with activities undertaken by government agencies or local bodies but also private sector, NGOs and the rural communities. - Reproduced.
Keywords: Rural development